WAYS TO IMPROVE THE ECONOMIC MECHANISM FOR INCREASING THE COMPETITIVENESS OF MINING ENTERPRISES IN THE TURKESTAN REGION - Kokеnova A.E.; Tulemetova, A.S.; Koptаyeva G.P.; Ongarova, G.T.; Satybaldina, A.T. (Scientific Journal of Pedagogy and Economics, 2020)
Increasing the competitiveness of enterprises in the world and domestic markets will make a huge contribution to the effective development of the country as a whole based on strategic analysis. It should be noted that the competitiveness of enterprises of this industry and their products depends not only on the conditions of the world market, but also on the degree of Organization of production of enterprises within the country. An important source of solution to this problem is the support of the state in the implementation of effective methods of industry management, new approaches to the organization of production, achievements of Science and scientific and technological progress in production. In the context of limited opportunities of society, despite the maximum support of the state, it remains a serious problem to increase the resource potential of enterprises based on strategic analysis, increase the material and technical level, its industrialization, and use of intensive innovative technologies in the near future. Thus, all of the above determined the relevance of the topic of the scientific article and its importance in the development of the country’s economy. At the same time, despite the high relevance of the issue and the depth of scientific research, there is a lack of systematic approach and a lack of comprehensive consideration from a modern economic point of view. Also, in many theoretical aspects, only individual studies are devoted to the methodological and practical aspects of the formation of market conditions. Therefore, in order to replace it, there is a need to solve the issues of improving the economic efficiency of industrial enterprises by improving the economic mechanism for increasing the competitiveness of enterprises.